Methodological Approaches to Learning Traditional Singing and Playing: A Case Study from the Faculty of Education in Sombor - Jović Vujaković, Filip (Norma, 2026)
This paper examines the methodological approaches used in teaching the course Choir and Orchestra at the Faculty of Education in Sombor, with a particular focus on the role of traditional singing and instrumental performance in the development of students’ performance and pedagogical competencies. Through the analysis of teaching practice and course content, the study highlights the importance of integrating elements of intangible cultural heritage into the educational process with the aim of enhancing musical literacy, expressiveness, and methodological preparedness of future teachers. The theoretical framework is based on contemporary music pedagogy models that emphasize experiential learning and cultural context. The findings indicate that such approaches not only enrich music instruction but also contribute to the preservation of cultural identity and the improvement of the overall quality of music education.
Keywords: education; teaching methodology; traditional singing; traditional instrumental music; Choir and Orchestra